A future without health? Health dimension in global scenario studies - Pim Martens; Maud Huynen
This paper reviews the health dimension and sociocultural, economic, and ecological determinants of health in existing global scenario studies. Not even half of the 31 scenarios reviewed gave a good description of future health developments and the different scenario studies did not handle health in a consistent way. Most of the global driving forces of health are addressed adequately in the selected scenarios, however, and it therefore would have been possible to describe the future developments in health as an outcome of these multiple driving forces. To provide examples on how future health can be incorporated in existing scenarios, we linked the sociocultural, economic, and environmental developments described in three sets of scenarios (special report on emission scenarios (SRES), global environmental outlook-3 (GEO3), and world water scenarios (WWS)) to three potential, but imaginary, health futures ("age of emerging infectious diseases", "age of medical technology", and "age of sustained health"). This paper provides useful insights into how to deal with future health in scenarios and shows that a comprehensive picture of future health evolves when all important driving forces and pressures are taken into account.